The Threefold of Academia Europeana: A Case of Universitas Vilnensis - Šaulauskas, Marius Povilas; Bumblauskas, Alfredas (Problemos, 2009)
The article argues that universitas or Academia Europeana is, first and foremost, a category of value and not an economic, professional or political entity. Axiological structure that unites the university habitat is threefold. It consists of the three clusters of values coming from the different epochs. First, polylogue of the Middle Ages based on the principle of multicentrism and unmediated, face to face sharing of competence. Second, modern statism and scientism founded in the national monocentrism and a combination of mediated, written, and unmediated, verbal, sharing of competence. Third, modern economism and globalism supported by the national monocentrism and the instrumentation of mediated sharing of competence. It has been showed that Vilnius University possesses all three value clusters, while the idea of the millennium of Lithuania serves as an impetus to conceptually recapture the historic experiences of Vilnius University. The article shows that the three value formations of the Academia Europeana in the history of Vilnius University, which is posited as the extreme edge of the European university habitat, underwent an essential, even extreme, radicalization. It has been argued, that sustainable development of university education is unthinkable without the consonant development of all three historically formed clusters of values, the most important of which still continues to be centered around the tradition of classical polylogue – unmediated search for existential values that is carefully passed on from hands to hands and from generation to generation.